Plant water relations of selected species in wet and dry tropical lowland forests in Costa Rica - Oberbauer, Steven F. (1985)
The water relations of early and late-successional plant species of pre-montane wet forest and lowland dry forest in Costa Rica were compared during the dry season. Early-successional species had higher stomatal conductances (g) than late-successional species at both sites. The same pattern did not hold for plant water potentials (ψ). A wide array of daily patterns of ψ and g was found among species of the same successional status. Midday stomatal closure was found in more than half of the wet forest species and nearly all of the dry forest species examined. Despite the absence of substantial rainfall for several months, all species in the dry forest with expanding leaves at the time of sampling had predawn ψ values that were above -1.0 MPa, indicating available sources of soil water.